Social Conformity and Bounded Rationality in Arbitrary Games with Incomplete Information: Some First Results - Edward Cartwright; Myrna Wooders (Fondazione Eni Enrico Mattei (FEEM), 2003)
In has been frequently observed, in both economics and psychology, that individuals tend to conform to the choices of other individuals with whom thy identify. Can such conformity be consistent with self-interested behaviour? To address this question we use the framework of games with incomplete information. For a given game we first put a lower bound on e so that there exists a Nash e-equilibrium in pure strategies consistent with conformity. We also introduce a new concept of conformity that allows players to conform and yet perform different actions. This is achieved by the endogenous assignment of roles to players and by allowing actions to be conditional on roles. We conclude by relating our research to some experimental literature.
Keywords: C70; 330; Social Conformity; Bounded Rationality; Arbitrary Games; Verhaltensökonomik; Begrenzte Rationalität; Bayes-Statistik; Theorie; Wiederholte Spiele